Pembekalan Calon Tenaga Kerja Pada Balai Latihan Kerja Barito Kuala Kalimantan Selatan - Muhammad Risanta; Adista Anjar Diany; Meiske Kristin Lumanauw (NEAR: Jurnal Pengabdian kepada Masyarakat, 2024)
Labour market competition is getting tighter due to the imbalance between the number of jobs and job seekers. This service aims to provide inadequate knowledge and skills at the youth level. The balance of hard skills and soft skills is the key to success in facing technological developments and globalisation. This activity consists of a series of trainings designed to provide hands-on experience to prospective workers. The expected results are increased self-confidence, strengthened understanding of skill combinations and career readiness.